Potential land transformation threats to the distribution range of the Cheetah, Acinonyx jubatus, in South Africa - Sibanda, Mxolisi (My University, 2011)
Various conservation landscape strategies such as hotspots and ecoregions are directed at ensuring the persistence of a range of species or biodiversity. However some individual species require special attention because of specific threats. The IUCN Red List system has ensured the ensuring the inclusion of a variety of threats in the Red listings and consequently conservation planning. This study evaluated present and future threats on the globally Vulnerable (VU C2a.1) Cheetah (Acinonyx jubatus, Shreber, 1775) in South Africa. The following threats were integrated to assess the overall threat to Cheetah in its regional extent of occurrence (EOO) in South Africa; fragmentation, agricultural land use, forestry and human population density. The analysis showed favourable and unfavourable land fractions for cheetah persistence across the EOO. Forestry and agriculture were the major transformation threats in the KwaZulu-Natal (KZN) region. Human population threat was greatest at the edges of the protected areas and in the KZN. This may indicate increased threat for the future with more demand for land by people. This highlights the challenge of integrating cheetah conservation into the land use planning process as a legitimate land use. This can be achieved through community based conservation in the EOO. Such initiatives should also involve other stakeholders such as commercial wildlife farmers, cheetah conservation entities like De Wildt and the Parks Authorities. Fragmentation was measured using the software FRAGSTATS and did not raise any major concern. Using this newly derived information does not seem to alter the placement of the species in the Vulnerable (VU) IUCN Red List category because fragmentation is not a threat.